MapRank: Geographical Search for Cartographic Materials in Libraries - Oehrli, Markus; Zollinger, Susanne; Siber, Rosi; Přidal, Petr (D-Lib magazine, 2011)
Describes a web-based geographical search system (geosearch) developed for the Swiss research portal for maps, which analyses the geographical coordinates of MARC21 field 034 and enables cartographic material to be found quickly and efficiently on the basis of its location and spatial extent via an intuitively accessible user interface, using a ranking algorithm (MapRank®) and an innovative indexing mechanism. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.